The Impact of Performance Measures in Football Players’ Transfer Market Value - Ferreira, Miguel da Silva Brito Pacheco (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence